PENINGKATAN PEMAHAMAN KONSEP KELILING DAN LUAS BANGUN DATAR PADA SISWA KELAS VII-2 MTsN 28 JAKARTA DENGAN MENGGUNAKAN ALAT MEDIA REALIA - Erna Sari Agusta (Balai Diklat Keagamaan Jakarta, 2020)
This classroom action research answers three questions, namely (a) Is there an increase in the ability to understand the concept of circumference and area of flat shapes by using real media? (b) How is the use of real media increase understanding of circumference and area of flat shapes? The study was conducted in two cycles. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The subject of this research is students of class VII-2 MTsN 28 Jakarta. Data were collected through questionnaires, teacher and student activity questionnaires, formative test, and teaching and learning activity observation sheets. Data were analyzed descriptively using descriptive statistics and qualitative analysis. The results showed that the students' ability to understand the concept of the circumference and area of a flat shape increased from cycle I to cycle II. In the first cycle of meeting 1 (31.6%), the first cycle of meeting 2 (55.8%), the second cycle of meeting 1 (71.1%), the second cycle of meeting 2 (92.1%). The conclusion of this study is the use of real media can increase understanding and have a positive effect on understanding of circumference and area of flat shapes. The research recommends that teacher can use real to better teaching in the curriculum area.